Endometrial Histomorphometry of Anestrous Mares Under the Influence of Different Embryo Transfer Hormonal Protocols - Silva, Elisa S.M.; Leite, Raíssa O. [UNESP]; Maciel, Luciana F.S. [UNESP]; Francia, Camila C.D.A. [UNESP]; Padovani, Carlos R. [UNESP]; Oliveira-Filho, José P. [UNESP]; Meira, Cezinande [UNESP] (Elsevier, 2019)
Aiming to investigate the effects of different hormonal protocols on the endometrium morphometry of anestrous mares, 26 animals were assigned to four different treatment groups: (1) EB2.5LAP4: single dose of 2.5 mg of estradiol benzoate (EB); (2) EB5LAP4: 5 mg of EB in 2 consecutive days; (3) EB10LAP4: 10 mg of EB in three consecutive days, considering that all EB-treated groups received a single dose of 1,500 mg of long-acting progesterone (LA P4) after the single/last EB dose; and (4) LAP4: only 1,500 mg of LA P4. Results were also compared with those found in cyclic mares (control group). Endometrial biopsies were collected before and after the hormonal treatments in anestrous mares, and during estrus and at 5 days after ovulation in cyclic mares (D5). Samples were prepared for histological and histomorphometric analysis. Tissue sections were examined to determine luminal epithelium height (LEH), glandular epithelium height (GEH), endometrial thickness (ET), and glandular density (GD). Similar morphometric changes were observed after EB and P4 were administered to groups EB5LAP4 and EB10LAP4. Five days after LA P4 administration (D5), all the assessed variables were similar between all EB-treated groups. In addition, all variables of the EB-treated groups were similar to the control group on D5. Although most of the LAP4 group variables on D5 were similar to the EB-treated groups (except GD), reduced GD and GEH were found when compared with the control group, demonstrating the importance of estradiol priming before P4 on glandular activity and density.
Keywords: Endometrium; Histomorphometry; Hormones; Noncyclic mares